Removal of Color and Turbidity in Runoff Water using Coconut (Cocos Nucifera) Endocarp Activated Carbon - Azabache Liza, Yrwin F. (2022)
The aim of this research was to determine the efficiency of activated carbon obtained from coconut (Cocos nucifera) endocarp in the reduction of color in runoff water to improve its quality. For this purpose, activated carbon was produced at a carbonization temperature of 700 °C in a time of 30 minutes and phosphoric acid at a concentration of 85% was used as an activating agent. A completely randomized design was used, consisting of 3 treatments (100, 50 and 25 g of activated carbon) and a control (without treatment), with three replicates of each treatment, where 1 L of water from the uptake was filtered. It was determined that the best percentage removal was obtained with treatment 3 (T3) in the reduction of color and turbidity with average values of 97.56% and 97.11%, respectively. An activated carbon filter was installed in the San Lorenzo - Moyobamba sector in a similar way to the laboratory tests, in which the efficiency of this product in reducing the color and turbidity of the water was demonstrated, achieving values suitable for human consumption.